2020
DOI: 10.1128/iai.00759-19
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells TargetingLactobacillus plantarumStrain NC8 with a Surface-Displayed Single-Chain Variable Fragment of CD11c Induce an Antigen-Specific Protective Cellular Immune Response

Abstract: Influenza A virus (H1N1) is an acute, highly contagious respiratory virus. The use of lactic acid bacteria (LAB) to deliver mucosal vaccines against influenza virus infection is a research hot spot. In this study, two recombinant Lactobacillus plantarum strains expressing hemagglutinin (HA) alone or coexpressing aCD11c-HA to target HA protein to dendritic cells (DCs) by fusion to an anti-CD11c single-chain antibody (aCD11c) were constructed. The activation of bone marrow dendritic cells (BMDCs) by recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A number of bacterial vectors, such as attenuated Salmonella ( 18 ) and probiotic lactic acid bacteria ( 19 ), have been used to deliver protective antigens through an oral immunization approach. In particular, Roy Curtiss III’s lab developed a series of Salmonella strains and vectors with novel features to enhance immunogenicity, including regulated delayed synthesis of heterologous antigens ( 20 ) and regulated delayed attenuation ( 21 ), which provide the vaccine strain with a nearly wild-type ability to colonize lymphoid tissues before exhibiting an attenuated phenotype, thereby leading to the development of strong immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…A number of bacterial vectors, such as attenuated Salmonella ( 18 ) and probiotic lactic acid bacteria ( 19 ), have been used to deliver protective antigens through an oral immunization approach. In particular, Roy Curtiss III’s lab developed a series of Salmonella strains and vectors with novel features to enhance immunogenicity, including regulated delayed synthesis of heterologous antigens ( 20 ) and regulated delayed attenuation ( 21 ), which provide the vaccine strain with a nearly wild-type ability to colonize lymphoid tissues before exhibiting an attenuated phenotype, thereby leading to the development of strong immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…After mucosal administration, LABs and nanoparticles generate mucosal responses against entrapped antigens [ 161 , 162 , 163 , 164 ]. To improve their efficacy, LABs such as lactobacillus have been coupled with DC targeting peptides; alternatively, complement C3d3, anti-CD205, anti-CD11c, or neonatal Fc receptors (FcRn) have been expressed at their surface [ 165 , 166 , 167 , 168 ]. Nanoparticles such as poly(lactic-co-glycolic acid) and liposomes have also been functionalized with anti-DEC-205 [ 169 ], anti-CD40 [ 170 ], anti-mannose receptor [ 171 ], or anti-CD11c [ 172 ] antibodies to target them to DCs.…”
Section: Stxb Functions As a Mucosal Delivery Vectormentioning
confidence: 99%
“…16,17 While the underlying mechanisms remain largely unknown, many studies have shown that L. plantarum prevents virus infection and reduces cell inflammation by enhancing innate immunity, regulating gut microbiota, 14,18 inhibiting virus replication, 19,20 and modulating cytokine production. 21 Exopolysaccharides (EPS) produced by LAB have various biological activities. They can protect bacterial cells from environmental effects such as desiccation and heat and acidic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 While the underlying mechanisms remain largely unknown, many studies have shown that L. plantarum prevents virus infection and reduces cell inflammation by enhancing innate immunity, regulating gut microbiota, 14,18 inhibiting virus replication, 19,20 and modulating cytokine production. 21…”
Section: Introductionmentioning
confidence: 99%